Interstate Cooperation in Violations of International Human Rights Law: The Case of Extraordinary Rendition - Necdet Umut Orcan (Public and Private International Law Bulletin)
Following the 9/11 attacks, the United States, specifically the Central Intelligence Agency (CIA), implemented a Rendition, Detention and Interrogation Programme, which involved capturing, unlawfully detaining, and interrogating individuals suspected of involvement in the War on Terror. The United States could not carry out these extraordinary renditions and interrogations alone. The Programme required the use of other countries’ territories for the unlawful rendition and interrogation of persons, as it could not be carried out within the United States legal system, which provides effective procedural safeguards for the apprehension, detention and interrogation of individuals. Cooperation with other states was necessary during the rendition and interrogation stages. Although the international community was aware of the unlawful procedures involved in the Programme from the beginning, at least 54 states, ranging from those considered to have been ‘advanced’ in terms of democracy and human rights to those with problematic records in this regard, cooperated with the CIA. This study investigates the reasons for cooperation between states in the practice of extraordinary rendition. It finds that the perception of national security as a priority over human rights is the main driver of such cooperation. The purpose of this study is to examine the practice of extraordinary rendition and assess it under human rights law. Then, after listing the states that cooperated with the CIA, it attempts to answer the question of why cooperation might have existed.